Enduring injustice: Memory politics and Namibia's genocide reparations movement. (October 2018) - Hamrick, Ellie; Duschinski, Haley
This article examines post-colonial memory politics in contemporary Namibia. It analyzes the ways in which ethnic Nama and Herero genocide reparations activists struggle to include Germany's colonial-era genocide of their communities in the national narrative of the contemporary Namibian state. In this article, we explore the extent to which the dominant political party, SWAPO, defines the state through the production of a hegemonic narrative about the Namibian past. We examine how this political context shapes the reparations movement's strategies and tactics, with attention to how different activist groups position themselves and their historical narratives with respect to the state. We then consider the importance of memorialization for the reparations movement and the multiplicity of meanings associated with state monuments. By highlighting the importance of memory for reparations activists, the article examines the way in which reparations claims shape and are shaped by the politics of memory production in the post-apartheid memory state.